Bulgaria : Public Expenditure Review for Agriculture and Rural Development - World Bank (World Bank, 2012)
Although Bulgaria now implements the European Union's (EU's) "common" agricultural policy (CAP), national policymakers still maintain responsibility to tailor CAP implementation to meet the specific development needs of the country. The National Rural Development Program (NRDP) very appropriately lays out the challenges that Bulgarian agriculture and rural development face, but the early implementation of a relatively high number of support schemes falls short of adequate administrative capacities and planning. With CAP resources projected to increase substantially over the coming years under pillar two, Bulgarian authorities must take appropriate corrective measures now so that the opportunity to impact long-term sector growth is not missed. The major challenge facing Bulgaria's rural sector is the significant fragmentation of land ownership and the highly polarized farming structure. As of 2003, there were 665,500 agricultural holdings operating in Bulgaria. About 75 percent of agricultural holdings account for less than 7 percent of the utilized agricultural area (UAA). They cultivate plots of no more than one hectare. In contrast, about 78 percent of UAA is farmed by 0.8 percent of holdings. The fragmentation of land ownership is a significant barrier to long-term investments in agriculture, land improvements, and efficient use of agricultural machinery. Other challenges facing the sector include: an aging labor force (54.6 percent aged 55 and over); relatively few young farm-holders (less than half the EU average); low educational attainment of those employed in agriculture; low labor productivity due to worn-out assets and outdated technologies; and poor access to credit for small and medium-sized producers.